VOLATILITAS NILAI TUKAR RUPIAH TERHADAP DOLAR AS DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI INDONESIA (PENDEKATAN COINTEGRATION DAN ENGLE GRANGER-ERROR CORECTION MODEL) - Muhammad R Assel; Maria Katje Tupamahu (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
The research and study cover a theoretical discussion and empirical study on Volatility Of Rupiah Exchange Rate to Us Dollar And Factors that it Influence based on Quartely data from Q12001 to Q42015 . The research employs the Cointegration and Engle Granger-Error Correction Model (ECM) approach by applying the Ordinary Least Square (OLS) method. The ECM is performed to anticipate the possibility of errors and disparity between the theoretical model and the statistical model as well as to identify long-term balance and validity of the model employed in the research. The research results indicate that within a long-term period, there is balance between changes in the rupiah exchange rate and macro-economic variables, i.e. interest rate and inflation within the observed period. On the other hand, within a short-term period changes in the rupiah exchange rate are affected significantly by interest rate, inflation and the ECT variable. Within such a period, PDB, and M2 variables do not significantly affect the volatility of rupiah exchange rate. Thus, it can be concluded that the rupiah exchange rate tend to respond to changes occurring in macro-economic variables, especially interest rate and inflation.